Museum and gallery education: promoting activities and practices in visual art education / Hazlin Anita Zainal Adidin - Zainal Adidin, Hazlin Anita (2012)
Art museums and art gallery all around the world have gallery education departments and run programmes that working closely with artist, artist educators, teachers and community leaders. Gallery and museum education continues to develop in response to changes in art practice, changes in audience needs and changes in formal and informal education. The research makes a case of exploring new possibilities to promote gallery and museum education to children and student in Malaysia and at the same time encourage art educators to directly involved in gallery and museum education in informal ways via gallery and museum education module that related to curriculum that has been teach in the classroom. In this case study, researcher will be focusing on University of Malaya Art Gallery and Museum of Asian Art of University of Malaya and how they work within designated module. Results of the study, museum and gallery education have an impact not only to students’ but also provide a positive perspective to educators. Both experiential learning and aesthetic learning are the best ways to provide students’ and children. By promoting collaboration and teacher training, gallery and museum not only to change the perception of educators’, but it gives a positive impact teaching and learning process.